STRATEGI PENGELOLAAN ASET WAKAF DALAM MENGURANGI TINGKAT PENGANGGURAN DI JAWA BARAT - Anisa, Siti; Kurnia, Tuti (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2024)
The purpose of this research is to determine waqf asset management strategies in reducing unemployment in West Java. The method used is qualitative with a descriptive approach and the determination of waqf management strategies using SWOT analysis techniques. The sample in this study was determined through puposive sampling. The data collection process is carried out through interview techniques and questionnaire distribution. The results of this study indicate that the management of waqf assets in West Java is still mostly used for worship purposes, namely waqf mosques and musolah.  Meanwhile, the management of waqf assets by BWI West Java does not exist to overcome unemployment so that the appropriate strategy in managing these waqf assets is the strategy of developing waqf land by establishing a Job Training and Competency Center, developing waqf land by establishing a labor channeling institution, developing waqf land by establishing a job vacancy information institution, developing mosque waqf by setting up kiosks to increase trade businesses, developing agricultural waqf by empowering the surrounding community to increase agricultural businesses and developing waqf land by empowering livestock businesses